Analysis of Development Patterns of Built Land and Spatial Structure in Bandung City Using Landsat 8 Image Data - Mukhoriyah Mukhoriyah; Samsul Arifin; Esthi Kurnia Dewi; Silvia Silvia (School of Postgraduate Studies, Diponegoro Univer, 2021)
The development of an urban area and the increasing totally of population growth greatly affect the need for land. To satisfy these needs, the land changes into built land which causes the density of an area. This study aims to analyze the development pattern of built land and the spatial structure of Bandung City. The data used are the 2015-2020 Landsat 8 time series imagery, the 2019 SPOT-6 imagery, and the administrative boundary map. The analytical methods used to identify and differentiate between built and non-built land classes are NDVI (Normalized Difference Vegetation Index) and the OTSU method with a threshold of 0.1. Based on the analysis, the results obtained are that the changes in the area of built and non-built land in 2015 amounted to 7,115.9 Ha and in 2017 it was 5,977.3 Ha and for 2 years the area decreased by 4%. Meanwhile, in 2017-2019 there was an increase of 2%, and in 2020 it decreased by 2% again. Based on the results of the analysis, the development pattern of land developed in the city of Bandung generally spreads from the city center to the suburbs, which are used as service / government centers, trade and service areas, and infrastructure. With this spreading pattern, the spatial structure is in the form of multiple nuclei or evenly distributed throughout the city of Bandung, where the City Center or CBD is used as a landmark for the surrounding areas. The high development pattern of built land has an impact on the surrounding environment, especially residential areas that have high building density causing the settlement area to become slum and reduce water catchment areas. The conclusion of this study is that the changes in the built-in land from 2015-2020 decreased by 3%, with the development pattern of the constructed land spreading out following the form of the road network, both arterial, collector and local roads.